Insights into Rural Consumers’ Perceptions on Digital Payment Systems - Jayaraj Mary Metilda; Sarkar Bibek (ITM Web of Conferences)
This study uses structured questionnaires to determine the factors that affect rural Indian consumers’ adoption of bank-launched electronic payments products. The paper aims to identify certain demographic characteristics that influence digital payment and to uncover dimensions of factors that influence digital payments in the rural set up. Data was collected form 200 respondents from the rural districts of Assam and Nagaland. Descriptive statistics was used to analyze the demographic variables. To uncover factors influencing the digital payment system, a factor analysis of variables identified was used and three factors literacy, technology and reliability and perception and concerns were identified and tested for reliability of the items to be measured. We propose future research in the identified variables using the tested measurement scales.